2018
DOI: 10.1159/000488988
|View full text |Cite
|
Sign up to set email alerts
|

RANKL/RANK/OPG Axis Is Deregulated in the Cerebrospinal Fluid of Multiple Sclerosis Patients at Clinical Onset

Abstract: Objectives: Our study focused on the RANKL (receptor activator of nuclear factor-κB ligand)/RANK/OPG (osteoprotegerin) axis and selected proinflammatory/immunoregulatory upstream mediators in the peripheral blood (PBL) and cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients. Methods: PBL and CSF were collected from healthy controls (n = 35) and MS patients at the clinical onset of the disease (n = 33). In addition, PBL samples were obtained from relapse-remitting (RR)-MS patients (n = 30). Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…RANK RANKL (TNFSF11) is produced by activated T cells, osteoblasts and stromal cells and binds to RANK, or to a decoy receptor osteoprotegerin (OPG). The ratio of RANKL/OPG has been shown to be altered in the cerebrospinal fluid of MS patients at clinical onset and mRNA levels of RANK, RANKL and OPG are elevated in PBMC from individuals with relapsing-remitting MS 271 . Given the role of RANKL in bone erosion, attempts have been made to target this pathway in rheumatoid arthritis.…”
Section: Tnfmentioning
confidence: 99%
“…RANK RANKL (TNFSF11) is produced by activated T cells, osteoblasts and stromal cells and binds to RANK, or to a decoy receptor osteoprotegerin (OPG). The ratio of RANKL/OPG has been shown to be altered in the cerebrospinal fluid of MS patients at clinical onset and mRNA levels of RANK, RANKL and OPG are elevated in PBMC from individuals with relapsing-remitting MS 271 . Given the role of RANKL in bone erosion, attempts have been made to target this pathway in rheumatoid arthritis.…”
Section: Tnfmentioning
confidence: 99%
“…Using a cytokine array, the levels of astrocyte-derived secreted factors were quantified in supernatants from astrocytes exposed to melanoma CM in the presence or absence of Aβ. This analysis revealed that Aβ both stimulates astrocyte secretion of anti-inflammatory cytokines and suppresses astrocyte secretion of cytokines with known pro-inflammatory activity in the central nervous system (Figure 5g) 3039 , thus demonstrating that melanoma-secreted Aβ stimulates astrocytes to an anti-inflammatory phenotype.…”
Section: Mainmentioning
confidence: 89%
“…These data indicate the initial RRO dysregulation at intrathecal sites already at the outset of the disease. Additional analysis of plasma samples and peripheral blood mononuclear cells from patients with RR-MS revealed upregulation of chemokines CCL2 and CXCL12 as well as increase in sRANKL and sRANKL/OPG ratio with the disease progression (70). Another clinical study on MS patients found higher OPG and lower RANKL levels in serum of patients with RR-MS compared to those with SP-MS.…”
Section: Rro Axis and Multiple Sclerosismentioning
confidence: 94%
“…Through the parallel profiling of peripheral blood and cerebrospinal fluid (CSF), our group was the first to compare the levels of RANKL and OPG in control subjects and MS patients at clinical onset (70). It is important to stress that these naïve patients were excluded from the use of any immunomodulatory or immunosuppressive agents known to interfere with the RRO axis (71).…”
Section: Rro Axis and Multiple Sclerosismentioning
confidence: 99%